The effect of prior pressure-treatment on the transformation behavior of Fe-32%Mn-6%Si alloy - Tatar, C (Elsevier Science Bv, 2006)
The effect of the pressure on transformation behavior of Fe-32%Mn-6%Si shape memory alloy has been investigated by X-ray diffraction and differential scanning calorimetry (DSC) analyses. The transformation temperatures and physical parameters of the alloy have been changed by the applied pressure. The austenite start transformation temperature increases 10-30 K applied pressure. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: martensitic phase transformations; differential scanning calorimetry; thermodynamic parameters